Implementation of the Blended Learning Method in Mathematics Learning during the Covid-19 Pandemic - Issholikhah, Lailatun Nissa; Harwati, Harwati; Shalikhah, Norma Dewi (Prosiding University Research Colloquium, 2022)
The rapid spread of COVID-19 in Indonesia has caused all learning activities to be shifted online. Learning mathematics online encountered several obstacles and then implemented it using blended learning. This study aims to determine the implementation of the blended learning method in mathematics learning and the obstacles in the implementation of blended learning mathematics. The method used is qualitative with a descriptive approach. Data collection techniques are observation and interviews. The research subjects were the principal, 5th grade mathematician and 5th grade students. The research location was at MI Muhammadiyah Sriwedari. Muntilan Magelang. The results of this study are the implementation of learning at MI Muhammadiyah Sriwedari during the Covid-19 pandemic using Blended Learning, namely online learning using whatsapp and youtube media, while offline learning is carried out with strict procedures and short learning times, and is carried out in two shifts. In conclusion, this blended learning method can help educators and students to develop better in the learning process, according to learning styles, preferences in learning and the characteristics of students in receiving the material presented.